2021
DOI: 10.1111/pin.13185
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of IgG4‐positive cells in idiopathic multicentric Castleman disease and validation of the 2020 exclusion criteria for IgG4‐related disease

Abstract: Patients with plasma cell type idiopathic multicentric Castleman disease (PC‐iMCD) often show elevated serum IgG4 levels and IgG4‐positive cell infiltration in tissues due to overproduction of interleukin‐6, and may meet the diagnostic criteria for IgG4‐related disease (IgG4‐RD). Although PC‐iMCD has been listed as a major exclusion disease for IgG4‐RD, distinguishing between these diseases is challenging due to a lack of highly specific diagnostic biomarkers. In 2020, we proposed exclusion criteria of IgG4‐RD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 27 publications
(72 reference statements)
0
11
0
2
Order By: Relevance
“…iMCD is a rare lymphoproliferative disorder that is characterized by multiple lymphadenopathies with unknown etiology [ 17 ]. In particular, iMCD-NOS is a heterogenous entity, likely including undefined disease [ 11 , 18 , 19 , 20 , 21 ]. The present results show that IPL is likely to be a separate subtype of iMCD, along with iMCD-TAFRO and iMCD-NOS, given its unique clinicopathological characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…iMCD is a rare lymphoproliferative disorder that is characterized by multiple lymphadenopathies with unknown etiology [ 17 ]. In particular, iMCD-NOS is a heterogenous entity, likely including undefined disease [ 11 , 18 , 19 , 20 , 21 ]. The present results show that IPL is likely to be a separate subtype of iMCD, along with iMCD-TAFRO and iMCD-NOS, given its unique clinicopathological characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, an atopic history, including allergic rhinitis, asthma, and atopic dermatitis, is characteristic for IgG4RD [ 12 ]. Finally, several studies showed that elevated levels of IL-6, IgG, IgA, and IgM, increased CRP, anemia, and hypoalbuminemia are distinctive for iMCD [ 12 , 14 , 15 ]. The persistently elevated levels of serum CRP (≧1.0 mg/dL), IgA, or IgM are proposed as exclusion criteria for IgG4RD by the Japanese Pathology Study Group of IgG4-related disease [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…48 A thorough workup with serology, including serum immunoglobulin A and M, and C-reactive protein, may help rule out lymphoproliferative diseases, including CD. 49 Currently, it is unclear if gastric IgG4-RD can increase the risk of gastric malignancy. A Japanese observational study reported that 2/8 (25%) gastric IgG4-RD patients had concurrent malignancy, 15 although none of the case reports noted associated malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…While rare, Castleman disease (CD), an important mimicker of IgG4‐RD, can also present as a gastric mass 48 . A thorough workup with serology, including serum immunoglobulin A and M, and C‐reactive protein, may help rule out lymphoproliferative diseases, including CD 49 …”
Section: Discussionmentioning
confidence: 99%